Whither the African University? - Bekele Gutema (Ethiopian Journal of the Social Sciences and Humanities, 2015)
Universities that came into being largely in the second-half of the 20th century, to meet the demands of that time have now evolved significantly and are asking themselves about what they are and what they should be. They could not disentangle themselves from their history. They could not take initiatives to embark on the path of independence in terms of curricula and research agenda. The idea of university reform which is being undertaken for over a decade and a half now, is largely not an African initiative. It is an initiative of the World Bank and its stakeholders. Another aspect of that agenda is the plan to educate an overwhelming number of university students in the fields of science and technology. While the plan in favor of science and technology may not be bad in and of itself, could it address society’s problems holistically? If the new plan neglects the humanities and the social sciences, is this plan not forgetting the point that the humanities help to define the purpose of science and technology? Did concerned bodies, i. e. universities, professors and the public at large debate on this issue and set such an agenda or is it merely a political agenda driven by narrow political and economic interests that see knowledge as commodity and nothing more? Does the reform take into account internationalization? Are universities trying to carry out reform in such a way that internationalization is fostered or are they carrying out the reform only with the local situation under focus? What could be the consequences of such a top-down plan? If the African university wants to be a proper university working for the empowerment of the African people, it must have independence in setting its priorities through debates that involve all who are concerned. It should also have the academic freedom to pursue knowledge and the autonomy requisite to plan its own development in terms of admission, curricular development, and research priorities.